MO021ENHANCED MCP-1 RELEASE IN EARLY AUTOSOMAL DOMINANT POLYCYSTIC KIDNEY DISEASE. (29th May 2021) - Janssens, Peter; Decuypere, Jean-Paul; De Rechter, Stéphanie; Breysem, Luc; Van Giel, Dorien; Billen, Jaak; Hindryckx, An; De Catte, Luc; Baldewijns, Marcella; Claes, Kathleen; Wissing, Karl Martin; Devriendt, Koenraad; et al.
Abstract: Background and Aims: Autosomal dominant polycystic kidney disease (ADPKD) is caused by mutations in either the PKD1 or PKD2 gene. While kidney failure typically occurs in adulthood, the disease starts in utero. The best change of preserving renal function long term might be the use of agents with few side effects as early as possible. For this approach, both better early prognostic stratification and novel treatment options are needed. The pediatric phase of ADPKD, while kidney function is still normal and before significant tissue destruction has occurred could be the best stage both to identify and study prognostic biomarkers as well as to identify novel targets for early treatment. Copeptin (a surrogate for vasopressin), epidermal growth factor (EGF) ( a measure for functional tubular mass) and monocyte chemoattractant protein-1 (MCP-1) ( a chemoattractant for macrophages) are associated with severity and hold prognostic value in adults but remain unstudied in the early disease stage. Kidneys from adults with ADPKD exhibit macrophage infiltration, and a prominent role of MCP-1 secretion by tubular epithelial cells is suggested from rodent models. Method: A monocentric cross-sectional study in a tertiary referral center was performed. All consenting genotyped ADPKD patients attending the outpatient pediatric ADPKD clinic of the university hospital of Leuven and age, sex and BMI matched healthy controls were included between June and October 2017. Plasma copeptin, urinary EGF and urinary MCP-1 were evaluated. MCP-1 was studied in mouse collecting duct cells, human proximal tubular cells and fetal kidney tissue. Results: 53 genotyped ADPKD patients and 53 controls were included. Mean (SD) age was 10.4 (5.9) vs 10.5 (6.1) years (P=0.543), and eGFR 122.7 (39.8) vs 114.5 (23.1) ml/min/1.73 m2 (P= 0.177) in patients vs controls respectively. Outcome parameters in table. Plasma copeptin and EGF secretion were comparable between both groups. Median (IQR) urinary MCP-1 (pg/mg creatinine) was significantly higher in ADPKD patients (185.4 (213.8)) compared to controls (154.7 (98.0)) (P= 0.010). Human proximal tubular cells with a heterozygous PKD1 mutation and mouse collecting duct cells with a PKD1 knockout exhibited increased MCP-1 secretion triggered by fetal bovine serum. Human fetal ADPKD kidneys displayed prominent MCP-1 immunoreactivity and M2 macrophage infiltration. Conclusion: An increase in tubular MCP-1 secretion is an early event in ADPKD, long before kidney function decline and in children with few kidney cysts. MCP-1 is a promising early disease severity marker and a potential treatment target.